Insights into non-peptide small-molecule inhibitors of the PD-1/PD-L1 interaction: Development and perspective. (1st March 2021) - Wu, Xia; Meng, Yangyang; Liu, Lei; Gong, Guowei; Zhang, Haotian; Hou, Yunlei; Liu, Chunyang; Wu, Di; Qin, Mingze
Graphical abstract: Abstract: The development of immune checkpoint inhibitors has become a research hotspot in cancer immunotherapy in recent years. Anti-PD-1/PD-L1 monoclonal antibodies (mAbs), such as pembrolizumab and nivolumab have been approved for treating different types of cancer. Many peptides, peptidomimetics and non-peptide small-molecule inhibitors targeting the PD-1/PD-L1 axis have been published so far. In comparison with mAbs, small-molecule inhibitors have the potential to overcome inherent shortcomings of mAbs, such as poor oral bioavailability, low tumor penetration, and high manufacturing costs. In this article, we mainly review non-peptide small-molecule inhibitors of the PD-1/PD-L1 interaction, their cocrystal structures, docking studies, and biological activities are also included to guide future study. In addition, we propose several strategies for designing more effective small-molecule modulators of the PD-1/PD-L1 pathway.